O tratamento da argumentação em livros didáticos: uma contribuição para o trabalho com a oralidade em sala de aula - Silva, Izabel Maria Martins da (2009)
Studies focused on the discourse in the classroom, especially as an effort of argumentation in the construction of knowledge, it have been the main point for further studies by the researchers involved in educational processes. That type of discourse is divided into two parts: the teacher s action and other resources, which the teacher users as supporting the learning-teaching process. Among those resources, there is the textbook. Relying on the importance of the argumentation as an epistemic resource and the source of the students development of linguisticdiscoursive competences, this research aimed at that social-discoursive practice and its point of view for the textbook. Questioning how this instrument can contribute to the stablishment of a reflexive school environment, providing the argumentation, using theoretical pre-concepts and suggestions for the activities. The aim of this study is to analyze the treatment of argumentation on Portuguese language books from 4th to 5th grade Elementary school, observing whether the activities can contribute to the development of students argumentative competence. It has as theoretical reference Leitão (1999, 2000, 2001, 2002, 2003) with his statements about argumentation and its dimensions. Furthermore, Marcuschi (1986, 1996, 1997, 2001, 2003, 2004, 2005) with his relevant researches about orality/speaking, providing a strong base for the development of oral argumentation, from the junction of argumentation-orality, this research in a qualitative/descriptive context aims at knowing these authors epistemic contexts and others on the literature; also aims at drawing a parallel between the authors interviewed perspectives and the authors books analyzed. Finally it describes the activities of these books, proceeding according to the analysis aimed. The results suggest that these books relied on the linguistic theories based on the social-interactionist and enunciative nature of language related to the learning theories in social cultural bases. The didactic sequence followed by the authors allows a remarkable space to activities, which providing the oral and written argumentation. The authors of these books consider the phenomenon of language according to the practices of orality and literacy providing many moments at work with several textual generes, which are social, not only in activities of comprehension of reading but also in the textual, oral, and written production. These activities are proceded or succeeded by others (exchange of ideas, debates, attentive listening, theme exposition) most of the time, which can allow the introduction of an argumentative discourse, according to the analysis done. These authors understand argumentation as a process not as a product